Magnetic field induced metal–insulator transition in single nodal ring topological semimetals. (21st June 2018) - Yao, Haibo; Zhu, Mingfeng; Jiang, Liwei; Zheng, Yisong
Abstract: Our theoretical investigation indicates that an applied magnetic field can open a gap between the conduction and valence bands of a nodal line semimetal (NLSM), though it is a kind of gapless material in the absence of a magnetic field. The emerging bandgap depends sensitively on the strength and orientation of the magnetic field which implies a tunable and large anisotropy of magnetoresistance in such kinds of topological materials. Following such a theoretical finding, we predict that in some candidates of NSLMs with a single nodal ring, such as the materials of CaP3 family, a transition between metallic and insulating states driven by a magnetic field is possibly observed experimentally. Consequently, a magnetic field can be viewed as a novel mechanism for metal–insulator transition of solid materials, in additional to the well-known conventional ones such as the Anderson and Mott transitions.